Symmetry reduction for time Petri net state classes - Bourdil, Pierre-Alain; Berthomieu, Bernard; Dal Zilio, Silvano; Vernadat, François (Science of computer programming, 2016)
We propose a method to exploit the symmetries of a real-time system represented by a Time Petri net for its verification by model-checking. The method handles both markings and timing constraints; it can be used in conjunction with the widely used state classes abstraction, a construction providing a finite representation of the behavior of a Time Petri net preserving its markings and traces. The approach has been implemented and experiments are reported. •We propose a symmetry reduction method for Time Petri nets interpreted over dense time.•The reduction can be used with the well known state classes construction.•Nets are described compositionally, together with their symmetries.•A total ordering of equivalent transitions in a state class enables efficient computation of state class representatives.